2014
DOI: 10.1038/nclimate2411
|View full text |Cite|
|
Sign up to set email alerts
|

Characterizing loss and damage from climate change

Abstract: Item 10 of the provisional agenda Approaches to address loss and damage associated with climate change impacts in developing countries that are particularly vulnerable to the adverse effects of climate change to enhance adaptive capacity 1-Activities to be undertaken under the work programme A literature review on the topics in the context of thematic area 2 of the work programme on loss and damage: a range of approaches to address loss and damage associated with the adverse effects of climate change Note by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(114 citation statements)
references
References 44 publications
1
109
0
Order By: Relevance
“…The risk-based approach to extreme event attribution is inherently probabilistic and does not claim to attribute the specific event that inspired the study; indeed, in [12], the observed event was excluded from the analysis to avoid selection bias, and the results concerned observed changes prior to the event itself, and expected future changes, rather than the event itself. Such analyses are clearly useful for policy and planning, and potentially also for liability [11,44], if they can be established to be credible. However, for weather-related extremes, converting a weather question into a climate question by abstracting the particular event to an event class (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The risk-based approach to extreme event attribution is inherently probabilistic and does not claim to attribute the specific event that inspired the study; indeed, in [12], the observed event was excluded from the analysis to avoid selection bias, and the results concerned observed changes prior to the event itself, and expected future changes, rather than the event itself. Such analyses are clearly useful for policy and planning, and potentially also for liability [11,44], if they can be established to be credible. However, for weather-related extremes, converting a weather question into a climate question by abstracting the particular event to an event class (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Assessing the impact of climatic and other drivers of change requires a multi-disciplinary approach for careful attribution research (Huggel et al 2013;Hansen et al 2015). Here we first present the climate results from the simulations and then focus on trends most relevant for public health risks associated with extreme heat.…”
Section: Attribution Of Trendsmentioning
confidence: 99%
“…The fact that multiple meteorological variables, and factors such as vulnerability, exposure, and adaptation (Huggel et al 2013;IPCC 2012) influenced the public health and other outcomes of the 2006 severe heat wave suggests that a multivariate approach is required to assess the impact of this event (Fischer and Knutti 2012). High humidity heat waves, such as the 2006 event, have been found to be especially dangerous, accounting for 66 % of hospitalizations associated with heat waves in the Central Valley (Guirguis et al 2014).…”
Section: Impact On Health Sectormentioning
confidence: 99%
See 2 more Smart Citations